2021
DOI: 10.2147/ijgm.s300776
|View full text |Cite
|
Sign up to set email alerts
|

Combined Neutrophil-to-Lymphocyte Ratio and CURB-65 Score as an Accurate Predictor of Mortality for Community-Acquired Pneumonia in the Elderly

Abstract: Community-acquired pneumonia (CAP) is common among the elderly; it typically has a poor prognosis and high mortality. This study evaluated the factors predicting CAPrelated in-hospital mortality in the elderly to identify a simpler and more accurate predictor. Patients and Methods: This was a single-center, retrospective study. The data used in this study was collected from all older patients (≥65) with CAP admitted to our hospital between January 2012 and April 2020. Results: A total of 2028 older patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…It is characterized by high rates of mortality and morbidity, especially in elderly patients. NLR has demonstrated a strong predictive value concerning short- and long-term mortality, need for ICU admission and re-hospitalization [ 24 , 25 , 26 , 27 , 28 ]. Therefore, NLR correlated with post-CAP mortality better than traditional pneumonia scores (Pneumonia Severity Index, PSI; and Confusion, Urea, Respiratory rate and Blood pressure, aged 65 and older, CURB-65), WBC and CRP [ 24 ].…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
“…It is characterized by high rates of mortality and morbidity, especially in elderly patients. NLR has demonstrated a strong predictive value concerning short- and long-term mortality, need for ICU admission and re-hospitalization [ 24 , 25 , 26 , 27 , 28 ]. Therefore, NLR correlated with post-CAP mortality better than traditional pneumonia scores (Pneumonia Severity Index, PSI; and Confusion, Urea, Respiratory rate and Blood pressure, aged 65 and older, CURB-65), WBC and CRP [ 24 ].…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
“…The remaining 27 studies were further scrutinized by reading the full text. Finally, only 10 studies were included in this meta-analysis [18][19][20][21][25][26][27][28][29][30]. 6 reported the predictive AUC value on 30-Day Mortality [19,21,[25][26][27][28] (of which 4 studies reported admission NLR levels, one study reported NLR at 3-5 days and 1 study reported both), 4 reported the mean NLR Values of survivors and 30-day non-survivor groups [19,20,25,26] (of which two reported admission NLR levels and two have reported both admission and 3-5 days NLR), and 3 reported the mean NLR Values of survivors and In-Hospital non-survivors groups [18,29,30] (All of which only reported admission NLR levels).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Three studies have evaluated the mean+-SD NLR admission values in the survivors and In-Hospital non-survivors [18,29,30]. Meta-analysis of these studies showed a significant difference in the NLR between the survivors and in-hospital non-survivors (SMD = 1.053, 95% confidence interval (CI) = 0.813 to 1.294, P = <0.001) (Figure 3).…”
Section: Nlr and In-hospital Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that significant advances in global health have taken place, pneumonia is one of the most common infectious diseases requiring hospitalization and is associated with high morbidity and mortality 1,2 . SARS-CoV-2 (COVID-19), the 7 th CoV known after SARS-, CoV and MERS-CoV, is the pathogen of the ongoing new pneumonia epidemic that infects humans 3 .…”
Section: Introductionmentioning
confidence: 99%